(3GdMeGjI GdLfGFjI dMQeI GdMjGI GdNGUI (B/ s - (3NGdO UGOb Jhajb aGhis; (3TQja SjO cGed s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2019)
(3ojYO GdMb ai MQeI GdMjGI GdNGUI YUH GdoMQjI GdTNUjI(B: (3h QcjRI CSGSjI dMbhb GdEfSGf(B: (3hdG Tc Cf eaghe GdMjGI GdNGUI ef GdeaGgje GdfSHjI GdeQfI HeYfi Cf gPG GdMb jQJHW ai GdMbjbI HefXheI GdJbGdjO h GdKbGaI h Gdbje GdOjfjI GdSGFOI h GdfXGe GdSjGSi ai cd eLJeY(B: (3h dbO COi GdJWhQ GdYdei h GdJcfhdhLi Edi XghQ eNGWQ LOjOI Ydj MQeI GdMjGI GdNGUI ai eLGd GdeYdheGJjI(B: (3HGdEVGaI Gdi GdeNGWQ GdJbdjOjI(B: (3GdCeQ GdPi ChLH JONd GdeTQY ai cKjQ ef GdOhd dSf bhGfjf NGUI HLQGFe GdMGSH GdBdi h GdEfJQfJ(B: (3abO JONd GdeTQY GdLfGFi GdaQfSi hCUOQ GdbGfhf Qbe (B493 (3dSfI(B2018(3e(B: (3GdoeJYdb HMeGjI GdHjGfGJ GdTNUjI h YOd bGfhf GdeYdheGJjI h GdoMQjGJ(B: (3ceG ojYO GdbGfhf Qbe (B175 (3dSfI (B2018(3e GdeUQi GdoeJYdb HecGaMI LQGFe JbfjI GdeYdheGJ bO CJi HhbJg GSJLGHI dMGLI edMI dJbfjf LQGFe GdMGSH GdBdi h GdEfJQfJ HeUQs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFi, (B2019s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B401-449s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdLfGFjs; (3GdMQjI GdTNUjIs; (3GdMeGjI GdLfGFjIs; (3GdMjGI GdNGUIs; (3LQGFe GdGYJOGA Ydi GdMjGg GdNGUg s; (3eTQhYjg GdOdjd GdLfGFi ef GLgRg GdJUfJ hGdeQGbHg s; (3VeGfGJ GdeSGS HMb GdeJge s; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs